Exercise versus usual care after non-reconstructive breast cancer surgery (UK PROSPER): multicentre randomised controlled trial and economic evaluation - Bruce, J; Mazuquin, B; Canaway, A; Hossain, A; Williamson, E; Mistry, P; Lall, R; Petrou, S; Lamb, SE; Rees, S; Padfield, E; Vidya, R; et al. (BMJ Publishing Group, 2021)
Objective To evaluate whether a structured exercise programme improved functional and health related quality of life outcomes compared with usual care for women at high risk of upper limb disability after breast cancer surgery.